Analisis Jalur dan Aplikasinya dalam Menentukan Faktor yang Mempengaruhi Derajat Kesehatan Balita di Sulawesi Selatan - Wahida Sanusi; Sukarna; Elma Selviana Darwis (Journal of Mathematics, Computations and Statistics, 2020)
This study aims to apply path analysis and to determine how much the factors that influence the health status of children under five in South Sulawesi, both directly (direct effect) and indirectly (inderect effect). Analyze models and interpret the results. The data used is the data on the recapitulation of the health status of children under five in South Sulawesi Province in 2019. The variables used are the number of pregnant women 20-30 years (X1), the number of children under five who received full 6 months of breastfeeding from mothers who do not work (X2), in the womb (X3), babies who are affected by malnutrition in pregnant women aged 30-35 years (Y1), and babies who die in the womb (Y2). This study uses a two equation path model. This research starts from formulating structural model equations, calculating path coefficients simultaneously and partially, performing model simulations using SPSS 22 software, interpreting and concluding. The results of the study obtained two structural equation models; the significant level (α) for the simulation results is 5% or 0.05; explained that each sub-structure model tested simultaneously and partially had a positive and significant effect on the health status of children under five in South Sulawesi.Keywords: Path Analysis, two equation paths, direct effect, indirect effect